Proceedings of the 8th World Construction Symposium 2019
DOI: 10.31705/wcs.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of smart building concept to enhance sustainable building practice in Sri Lanka

Abstract: With the expansion of economic activities, sustainable development in construction industry got more attention worldwide. Hence, industry practitioners are more concerned on achieving sustainable construction goals to make more effective and efficient services. The Smart Building concept can be implemented with advanced building technologies to achieve clients' requirements with in the economic, environmental and social parameters while enhancing building performances efficiently. To explore the applicability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Furthermore, Ghansah et al (2021) suggested that education informs engaging the professionals in training, conferences and workshops seminars, as it will help to improve the awareness and its adoption among the professionals. This corroborates the study of Bandara et al (2019), who mentioned that education and training could be used to enhance the awareness and total adoption of SBCs. The study of Agirbas (2020) emphasises the importance of SBCs on the simple effectiveness and attitude on education such as BIM.…”
Section: Smart Building Conceptssupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, Ghansah et al (2021) suggested that education informs engaging the professionals in training, conferences and workshops seminars, as it will help to improve the awareness and its adoption among the professionals. This corroborates the study of Bandara et al (2019), who mentioned that education and training could be used to enhance the awareness and total adoption of SBCs. The study of Agirbas (2020) emphasises the importance of SBCs on the simple effectiveness and attitude on education such as BIM.…”
Section: Smart Building Conceptssupporting
confidence: 90%
“…In Ghana, for example, Ghansah et al (2020) revealed that the level of awareness of SBC in construction firms among construction professionals is moderate and also noticed that there is a need for enlightenment on adopting SBC to improve energy efficiency, occupant comfort and sustainability. Also, in Sri Lanka, Bandara et al (2019) revealed that the benefits that can be derived from SBCs are long term, although most of the clients in the study area do not recognise the value of SBCs in terms of sustainability. Given this, the authors suggested improving the knowledge and awareness of professionals.…”
Section: Smart Building Conceptsmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, it is vital to consider looking at the benefits of SBT for successful adoption. Bandara, Abeynayake, and Pandithawatta [27] identify the benefit of SBT for project delivery in three sustainability goals: economic, social, and environmental. Sovacool and Furszyfer Del Rio [40] discovered that smart building's environmental benefits involve reducing greenhouse gas emissions, which is achieved through better monitoring of energy usage and control over carbon emission of CO 2 related materials in buildings.…”
Section: The Benefits Of Smart Building Technology In Developing Coun...mentioning
confidence: 99%
“…Accomplishing smart buildings requires promoting efficient technologies and the practice of smart buildings in the built environment [26]. Sustainable construction practices are crucial for achieving the three pillars of sustainable development namely economic, social, and environmental goals [27]. According to Vattano [28], sustainable building technology aims to provide a living and working environment that consumes fewer resources, produces less waste, and retrofits existing buildings to be innovative, energy-saving, and water-efficient.…”
Section: Introductionmentioning
confidence: 99%